Niger - land, climate, energy, agriculture and development: A study in the Sudano-Sahel Initiative for regional development, jobs, and food security - Rabani Adamou; Boubacar Ibrahim; Abdou Latif Bonkaney; Abdoul Aziz Seyni; Mamoudou Idrissa (University of Bonn, Center for Development Research (ZEF), 2021)
The Sahel is one of the most vulnerable regions to climate change in the world. Located in the central part, Niger is facing many complex and interconnected challenges which strongly hinder the achievement of the key sustainable development goals (SDGs). The high population growth rate (3.8% per year), weak infrastructure capacity, shortage of essential resources (including water, energy, food) coupled with the adverse impacts of variability and climate change threaten the population and reduce the country's economic growth efforts. With more than 77% of landmass area receiving less than 150 mm of precipitation yearly, and about 80% of the population depending on rainfed agriculture, water scarcity and dryness constitute serious constraints for the agriculture and livestock sectors. In addition, the unequal distribution of agricultural land and livestock worsens the poverty incidence among households, which is characterized by a GINI coefficient of 0.46 and 0.68 for land and livestock respectively. Access to drinking water remains very poor with high disparities between urban (64%) and rural areas (48%). Water sanitation amounting to only 2% in rural and 38% in urban areas, respectively, also remains a great issue. Elsewhere, several drought and flood episodes have negatively impacted agricultural productivity, causing recurrent famines and livestock losses. The situation is exacerbated by the impacts of land degradation, the advancement of desertification and also by climate change and variability threats, which are projected to increase in magnitude, intensity, duration and number over the country under all climate change scenarios. The country's high potential of renewable and non-renewable groundwater resources can be used for residential, agricultural and industrial purposes to overcome negative climate change impacts. Regarding the energy sector, the country is currently in an undesirable state, with very limited modern energy services (2% of the population), low electricity access (average rate of 18%, with around 10% in rural areas) and high dependency on traditional biomass (77% of primary energy consumption). However, the country is fortunate to have a tremendous amount of energy resources, including fossil fuels (oil, coal and gas) and renewables (solar, hydropower, and wind), that can be used to overcome many of the observed challenges and thereby contribute significantly in the achievement of various SDGs, including those related to affordable and clean energy, no poverty, and zero hunger. Indeed, in addition to resources for electricity production, Niger has a large surface water potential in the Niger River, with an average discharge of 6000 m3 /s and length of about 550 km, which can be mobilized for irrigation to enable food security. Therefore, socioeconomic development requires an integrated approach that brings all the key sectors into a common framework in order to solve the aforementioned challenges. Hence, in key development areas, several development policies and strategies from government, NGOs, and technical and financial partners have been initiated and implemented for inequality and poverty reduction to improve livelihoods in the country.
Keywords: O30; Q24; Q25; Q42; Q54; Q55; Q58; 330; Sahel; energy; climate change; land degradation; innovation; policy